Bidirectional crosstalk between the bone extracellular matrix and lysosomes in bone remodeling and osteoporosis - Zhou, Chang; Hu, Xinyue; Jing, Yichen; Zhang, Jiaheng; Tao, Jing; Ouyang, Xinyi; Tang, Jiaqian; Zhang, Guomin; Liu, Huiping (Frontiers in Endocrinology, 2026)
Osteoporosis is a systemic skeletal disorder characterized by progressive loss of bone mass and deterioration of microarchitectural integrity. Traditionally, its pathogenesis has been attributed primarily to an imbalance in the number and activity of osteoblasts and osteoclasts. However, emerging evidence has uncovered a critical bidirectional interdependence between the integrity of the extracellular matrix (ECM) and the functional homeostasis of the intracellular lysosomal system—an axis increasingly recognized as the “bone matrix–lysosome crosstalk.” Despite its apparent importance, the central role of this regulatory circuitry in bone homeostasis and the mechanisms through which it becomes disrupted under pathological conditions remain insufficiently defined.This review synthesizes current advances regarding the cell type–specific functions of lysosomes across distinct bone cell populations and further examines how the ECM, as a dynamic microenvironment, exerts reciprocal control over lysosomal biogenesis and activity. We highlight how the biochemical composition and biophysical properties of the ECM govern lysosomal acidification, metabolic coupling, and degradative capacity with remarkable precision. During the progression of osteoporosis, structural compromise of the ECM and lysosomal dysfunction reinforce one another, establishing a self-amplifying pathological loop that accelerates the collapse of the bone microenvironment. Recognizing this reciprocal deterioration, we propose that restoring the dynamic equilibrium of the “ECM–lysosome axis” may represent a mechanistic pivot for reversing osteoporotic degeneration. Interventions targeting lysosomal function, reconstructing the bone ECM, and employing nanomedicine-enabled organelle-specific delivery hold particular promise for advancing precision therapeutics in osteoporosis.